The Role of Women in Supporting the Economic Condition of the Poor: An Analysis of Gender Issues on Farming Families - Risdawati Siregar; Asnah Asnah (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Basically everyone agrees that women and men are different. Women and men in the household are generally subject to the division of labor. This division of labor led to the development of limited social roles for both sexes and the creation of power differences in some respects that were more favorable to men. This role is seen in poor families in Padang Bolak Tenggara District. Thus, research was carried out to find out more about the role of women in supporting the economy of poor households in farming families in the District of Padang Bolak Tenggara, the profile of women (farmer's wives) who worked, the time spent required by farmers' wives, and what gender issues arose due to the involvement of the farmer's wife in supporting the family's economy. This paper is a gender perspective. The essence of gender perspective research is a study that clearly seeks to express women's experiences and gender relations according to a central issue that needs attention. Data collection methods using observation and interviews. In conducting data processing and analysis, researchers use Harvard analysis techniques. This technique is often referred to as Gender Framework Analysis (GFA), which is an analysis used to look at the gender profile of a social group and the role of gender in development. Based on observations in the District of Padang Bolak Tenggara of the farming family, it is known that the farmer's wife is very involved in helping the family economy. The profile of women (farmers' wives) in the District of Padang Bolak Tenggara can be seen from the average age of 40-50 years, 65% have a junior high school education background, only 3 people who have makeup/salon and sewing skills, besides farming. The intensity of time spent by women (farmer's wives) working outside is quite high at around 8-10 hours per day. This still does not include homework, i.e. doing homework and caring for children. This makes the workload and working time span of farmer's wives much longer than men. Thus, the gender issue that arises is injustice in the division of labor.